Application of Numerical Taxonomy and Cluster Analysis in Ranking the Development Level of Tehran Districts Based on Cultural Tourism - Negin Hojjati; Hossein Zabihi; Zahra Sadat Saeideh Zarabadi (گردشگری فرهنگ, 2023)
Today, the concept of cultural tourism has drawn upon the factor of culture to facilitate development. The most important prerequisite to stress culture and culture-based industries necessitates a solid background.  Tehran, as the capital of Iranian civilization, has this advantage which can help the cultural tourism industry to contribute to urban development. However, the concept of cultural tourism is neglected in urban development plans. Therefore, the questions that arise include: a) what are the indicators of cultural tourism for the development of Tehran? b) How is the development in the 22 districts of Tehran ranked based on cultural tourism? This research is descriptive-analytical nature using a mixed approach to explain the framework of cultural tourism’s effectiveness on the development of Iranian cities. To this end, ranking the development status of the 22 districts of Tehran was carried out based on a road map to benefit from the hidden cultural treasures of Tehran by attaching cultural tourism to urban development plans.  This study employed documentary, and field study methods as data collection methods while content analysis, swing weighting, taxonomy-numerical, and cluster analysis were used as analytical methods. The results show that the 12th district of Tehran, with the most recorded places, and historical sites, Oud Lajan Bazaar, and Tehran Bazaar, have been given a higher priority compared to the rest districts of Tehran. Districts 6 and 1 of Tehran have had a better rank compared to other districts because of hotels and exhibitions of painting, photography, and sculpture and they have been ranked second and third respectively.